PENGARUH LINGKUNGAN KERJA DAN KESELAMATAN KESEHATAN KERJA (K3) TERHADAP KINERJA KARYAWAN ALIH DAYA (OUTSOURCING) PT. ISS INDONESIA AREA MALANG - Sukrispiyanto (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2024)
The purpose of this study was to find out and analyze whether the Work Environment and Occupational Safety and Health partially and simultaneously have a significant effect and to find out which variable is more dominant on the Performance of Outsourced Employees (Outsourcing) of PT. ISS Indonesia Malang Area . The data analysis technique used in this study is a quantitative method using SPSS version 22 software. This research uses validity test research, reliability test, regression analysis, multiple linear, determination test, partial test, and simultaneous test. Sempel in this study are outsourced employees of PT. ISS Indonesia Malang Area , the population used is 3 23 employees, because the population is more than 100 and researchers are guided by Arikunto (2006). the researchers took a sample of 25% of 3 23 employees so that the sample was 8 1 employees. P retrieval of primary data using a questionnaire. Based on the results of this study indicate that partially and simultaneously Work Environment and Occupational Health and Safety have a significant effect on Employee Performance . The Occupational Health Safety variable has a more dominant effect on employee performance. Keywords: Work Environment, Occupational Health Safety, Employee Performance.